2022
DOI: 10.1071/sh22081
|View full text |Cite
|
Sign up to set email alerts
|

Migrant and refugee youth perspectives on sexual and reproductive health and rights in Australia: a systematic review

Abstract: Migrant and refugee youth (MRY) in Australia face specific experiences that inform their sexual and reproductive health and rights (SRHR). Migrant and refugee communities experience poor health outcomes and low service uptake. Additionally, youth are vulnerable to poor sexual health. This review examines the understandings and perspectives of MRY. A systematic review was conducted as per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The protocol is registered with PROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
(441 reference statements)
0
10
0
Order By: Relevance
“…The lack of comprehensive SRHR education in the school curriculum reiterated at the microsystem level, is a systemic educational barrier that negatively impacts MRY’s understanding of and access to SRHR information and services (Aibangbee et al, 2023; Napier-Raman et al, 2023; Villa-Torres & Svanemyr, 2015). Various research including Villa-Torres and Svanemyr’s (2015) work consistently demonstrates the significant impact of SRH education on promoting safer sexual practices and mitigating health risks, as evidenced by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of comprehensive SRHR education in the school curriculum reiterated at the microsystem level, is a systemic educational barrier that negatively impacts MRY’s understanding of and access to SRHR information and services (Aibangbee et al, 2023; Napier-Raman et al, 2023; Villa-Torres & Svanemyr, 2015). Various research including Villa-Torres and Svanemyr’s (2015) work consistently demonstrates the significant impact of SRH education on promoting safer sexual practices and mitigating health risks, as evidenced by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Secrecy is a common manifestation of abortion stigma [ 52 ]. Moreover, many migrant and refugee communities maintain secrecy, silence and shame around SRH generally [ 7 , 10 ]. The taboos around abortion and the seeming contradictions between outward expression and actual practices seen in this review are therefore unsurprising.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that migrant and refugee populations often have inadequate SRH knowledge, attributed to limited SRH education in home countries, disruption of schooling, and stigma surrounding SRH within communities [ 7 ]. In this review, restricted discourse around SRH and lack of knowledge indicate that women’s agency and ability to make informed abortion decisions are impeded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations